Validation of Image Descriptions for the Children's Assessment of Participation and Enjoyment and Preferences for Activities of Children: A Delphi Study. (September 2022) - Perreault, Melanie; Belknap, Katriana; Lieberman, Lauren; Beach, Pamela
Introduction: The Children's Assessment of Participation and Enjoyment (CAPE) and the Preferences for Activities of Children (PAC) are useful measures to assess how children with visual impairments are meeting the nine areas of the expanded core curriculum (ECC). Each item of the CAPE and PAC includes an activity with an accompanied image to illustrate it. However, the measures do not provide standardized image descriptions for each item, which limits its validity and reliability for this population. Thus, the purpose of this Delphi study was to validate and standardize image descriptions for the CAPE and PAC so they can be used more effectively with children with visual impairments. Methods: The expert panel consisted of 11 professionals with extensive knowledge and experience with individuals with visual impairments and six dyads of parents and their child with a visual impairment. Each panel member assessed the accuracy of wording for 57 image descriptions on a 4-point Likert scale and provided feedback on items rated below 3. Results: Consensus on all image descriptions was reached after two rounds. Discussion: The results of this study help to increase the validity and reliability of the CAPE and PAC for children with visual impairments. Implications for Practitioners: The CAPE and PAC can be used more effectively by practitioners and researchers to assess the areas of the ECC for children with visual impairments.